Investigation on the Suitability of Metamorphosed Granite in Ilorin Nigeria for Road Construction and Polished Rock - Olatunji K.J.; Kamilu D.O.; Oladiti A.G; Akanji F.A.; Dauda H.O.; Ibrahim A.O.; Abubakar A.A.; Kolawole M.F. (Advances in Engineering and Technology: An International Journal, 2023)
The suitability of metamorphosed granite for road construction and polished rock were investigated. Samples were taken from zones of Man Hardi Quarry Ilorin using random sampling method. The samples were subjected to different test namely, chemical analysis, polish value, oxidation properties, compressive strength and hardness test. The average chemical analysis shows the silica contents for samples from zones A, B and C are 67.73%, 73.62% and 72.40% respectively, specific gravity obtained are 4.52, 4.80 and 3.60 for zones A, B and C. The oxidation properties test reported, with no peeling was observed, the polish stone value (psv) test for the samples showed result of good abrasiveness and produced attractive colour; the values for zones A, B and C are 90.88, 97.36 and 93.71 while respectively compressive strength test estimation obtained were 142.37, 201.62 and 164.62 MPa for samples from zones A, B and C. The Hardness test values are 85.59, 96.84 and 88.11 respectively. Hence, the value obtained from the investigation on the suitability of metamorphosed granites for road construction and polish rock shows that they are good for road constructional and production of polished stoneworks.